Metagenomic approach of associated fungi with megaplatypus mutatus (Coleoptera: Platypodinae) - Ceriani Nakamurakare, Esteban Daniel (2018)
Megaplatypus mutatus is a major forestpest in Argentina and an emerging pest in Europe. In this study the multitrophic interactions between M. mutatus and associated fungi were assessed with ametagenomics approach (454-pyrosequencing). A total of 270 collection pointsfrom insect galleries from three locations in Argentina were pooled for pyrosequencing analyses. Two hosts, Populus deltoides and Casuarina cunninghamiana, were independently evaluated to characterize the fungal communities associated to M.mutatus; compare the culture-independent approach with previous culturingstudies, in terms of data recovery related to the fungal community composition,and test the specificity of the fungal communities amongst locations and hosts. A Generalized Linear Mixed Model was performed to compare the fungal richnessin each dataset, which showed no significant differences between taxa richness amongst locations. Principal Coordinates Analysesshowed a separation between fungal communities within the same host, suggesting that host identity would not be crucial to determine the specificity in fungal communities. Candida insectalens and one Fusarium species, present in all hosts and locations, achieved 37.6 % of the total relative frequency per taxa. These results complement the data from culturing methods previously reported, thus improving the accuracy and understanding of the fungal assemblages associated to M. mutatus.